2021
DOI: 10.1161/strokeaha.120.030089
|View full text |Cite
|
Sign up to set email alerts
|

Deintensification or No Statin Treatment Is Associated With Higher Mortality in Patients With Ischemic Stroke or Transient Ischemic Attack

Abstract: Background and Purpose: Practice guidelines recommend that most patients receive moderate- or high-potency statins after ischemic stroke or transient ischemic attack (TIA) of atherosclerotic origin. We tested the association of different patterns of potency for prescribed statin therapy—assessed before admission and at hospital discharge for ischemic stroke or TIA—on mortality in a large, nationwide sample of US Veterans. Methods: The study population i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“… 4 After that, several randomized trials demonstrated the effect of statins on reducing the risk of recurrent stroke and major cardiovascular events in patients with a history of stroke. 28 Previous observational studies have associated the lack of statin therapy to increased short-term mortality 29 , 30 However, large-scale, long-term, follow-up studies of nonstatin users are not, for the best of our knowledge, available. We found that statin usage within the first 90 days after IS was associated with lower all-cause mortality and MACCE at both 1-year and 12-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“… 4 After that, several randomized trials demonstrated the effect of statins on reducing the risk of recurrent stroke and major cardiovascular events in patients with a history of stroke. 28 Previous observational studies have associated the lack of statin therapy to increased short-term mortality 29 , 30 However, large-scale, long-term, follow-up studies of nonstatin users are not, for the best of our knowledge, available. We found that statin usage within the first 90 days after IS was associated with lower all-cause mortality and MACCE at both 1-year and 12-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, patients with ESUS receive intensive lipid-lowering therapy (e.g., statins, ezetimibe) to achieve a level of LDL cholesterol <70 mg/dL (1.8 mmol/L) as early as possible after stroke (122)(123)(124). The treatment is maintained long-term if well-tolerated, even in older adults (125)(126)(127)(128). Specific targets of LDL cholesterol have not been assessed in patients with ESUS and it is unknown if the presence of an ipsilateral nonstenotic carotid plaque would modify the effect of lipid-lowering drugs as suggested by findings of the Stroke Prevention by Aggressive Reduction in Cholesterol Levels (SPARCL) (129).…”
Section: Other Therapies and Interventionsmentioning
confidence: 99%
“…Desire for ‘natural’ approach. Poor compliance and long-term adherence [ 356 , 357 ]. Unjustified fear of LLT medications [36] Mental health [358] Depression (associated and possibly causal [359] ), stress [360] , anxiety or anger syndromes [361] .…”
Section: Despite Many Recommendations Early Treatment Has Not Become ...mentioning
confidence: 99%